ANALISIS KERUGIAN DAYA PADA SALURAN TRANSMISI TEGANGAN EKSTRA TINGGI 500 KV DI P.T. PLN (Persero) PENYALURAN & PUSAT PENGATURAN BEBAN (P3B) JAWA BALI REGIONAL JAWA TENGAH & DIY UNIT PELAYANAN TRANSMISI SEMARANG (Jurnal Teknik Elektro, 2009)
Necessity of electric power in Indonesia straight rise agree with economic and industry development a long with society growth. Because of that, government must be well to give service of electric with SUTET 500 kV.In the distribution electric power from generation to load centre used transmission line, because distance from generation to load centre is so far. Electric power in flow, they have a power loss. It’s because factor of isolator leak and corona leak then the voltage will be down (voltage dropped) and for efficiency of transmission will be down too.The aim of this research is to calculate power loss in SUTET 500 kV. This calculates had been done three different times in SUTET Ungaran – Pedan at 15th-24th August 2007 07.00 am (lead has been started), 13.00 pm (lead has been changed from low to middle) and 18.00 pm (lead on the top). As the result of this calculate, at Wednesday, 15th August 2007 at 18.00 pm have the biggest value of power loss 6.179.710,62 Watt and the smallest power loss has been done in Wednesday 15th August 2007 at 07.00 am and Wednesday 22nd August 2007 at 07.00 am 2.816.691,632 Watt.The SUTET 500 kV Ungaran – Pedan efficiency value in good condition because the average approximately 100 %. Nevertheless, there are lack of the result because calculate only in ten days. The best way to reduce this lack is continuously calculation.Keywords :PowerLoss,Voltage Dropped, Corona